Scenarios and strategies for future‐proofing ecosystem management under climatic novelty - Lauren T. Toth; Elizabeth T. Borer; Deron E. Burkepile; Joan Dudney; Nathan P. Lemoine; Julianna J. Renzi; Kathryn E. L. Smith; Travis A. Courtney; Sara A. Goeking; William M. Hammond; David L. Hoover; Sandra MacFadyen; et al. (Conservation Biology, 2026)
Climate change is driving unprecedented declines in dominant, habitat‐forming foundation species across marine and terrestrial ecosystems globally. As climatic novelty becomes the norm, ecosystem reassembly will become increasingly common. Predicting and understanding these transitions, and their implications for future ecosystem functioning, is essential for designing effective forward‐looking management strategies. We explored 3 scenarios that describe a range of ecosystem reassembly trajectories following declines in previously dominant habitat‐forming taxa: compensation, in which functionally similar subdominant or immigrating taxa maintain ecosystem structure and function; decline, in which no compensation occurs leading to loss of ecosystem structure and function; and transformation, in which the ecosystem present historically can no longer persist and shifts into a fundamentally different ecosystem type with distinct structure and function. This range of potential outcomes highlights the urgent need to assess the ecological feasibility and functional implications of potential management actions. Scientists and managers can work together to quantify local‐scale climatic novelty and ecosystem resilience to better predict the most likely reassembly trajectories and identify management interventions that will optimize ecosystem function. This approach would allow for more proactive planning to support persistence of ecosystem structure and function, helping to future‐proof ecosystem management in a rapidly changing world.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

The COSPAR international space weather action teams (ISWAT) initiative: a driving force for the COSPAR space weather roadmap - Maria M. Kuznetsova; Mario M. Bisi; Hermann J. Opgenoorth; Martin A. Reiss; M. Leila Mays; Lucilla Alfonsi; C. Nick Arge; David Barnes; Anna Belehaki; Thomas E. Berger; Amanda Brecht; Sean Bruinsma; et al. (Advances in Space Research, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Incorporating drone imagery and field-data to assess geographic and social drivers of agroforestry biodiversity in western Ecuador - Sophia C. Roberts; Florencia Montagnini; Ryan L. Lynch; Jerry Toth; Simon A. Queenborough (Environmental Development, 2026)

Survival and reinfection rates of SCTLD-affected corals treated in situ with amoxicillin - Karen L. Neely; Robert J. Nowicki; Michelle A. Dobler; Kathryn A. Toth; Kevin A. Macaulay; Sydney M. Gallagher (Frontiers in Marine Science, 2025)
The unprecedented mortality to Caribbean corals caused by stony coral tissue loss disease (SCTLD) led to the use of an in-water medicine applied directly to disease lesions. This topical amoxicillin paste is highly effective in halting lesions and has been used on tens of thousands of wild corals since 2019, but long-term survival rates of treated corals as well as the frequency of potential reinfections remained speculative. We fate-tracked thousands of corals treated for SCTLD in the Florida Keys across numerous species and two habitats (inshore patch reefs and offshore spur and groove) every two months, assessing health condition and providing additional treatments if necessary. After three years, 84% of corals remained alive. Inshore corals had higher survival rates than offshore corals, and there were species-specific differences in survival, with the boulder corals Montastraea cavernosa and Orbicella faveolata having higher survivorship than brain coral species. Across all treated corals, 36% remained disease-free for at least one year after the initial treatment, and an additional 18% remained disease-free if any new lesions were treated within three months after the initial treatment. Reinfection rates were influenced by both habitat and species, with inshore corals more likely to remain disease-free than offshore corals. Among the species assessed, Montastraea cavernosa was the most likely to remain disease free, while the brain corals Diploria labyrinthiformis and Colpophyllia natans were the most prone to reinfection. These measurements can help guide expectations for disease intervention projects, including survival estimates if corals are regularly visited, as well as predictions of survivorship if diseased corals are visited only once or twice.

Evaluating the effectiveness of field-based probiotic treatments for stony coral tissue loss disease in southeast Florida, USA - Kelly A. Pitts; Mackenzie Scheuermann; Jonathan S. Lefcheck; Blake Ushijima; Natalie Danek; E. Murphy McDonald; Aaron R. Milanese; Monica D. Schul; Julie L. Meyer; Kathryn A. Toth; Zachary Ferris; Yesmarie T. De La Flor; et al. (Frontiers in Marine Science, 2025)
Stony coral tissue loss disease (SCTLD) has spread throughout Florida’s Coral Reef, causing extensive mortality of over 30 species of reef-building corals, and has rapidly spread to many other countries and territories throughout the Caribbean. Current treatments for SCTLD, including a proprietary paste mixed with the antibiotic amoxicillin, do not provide protection from future infections and may select for antibiotic-resistant pathogenic bacteria. In contrast, beneficial microorganisms (i.e., probiotics), may directly treat or act as prophylactics for corals exposed to SCTLD. This study investigated the use of the bacterium Pseudoalteromonas sp. McH1-7, previously isolated from a SCTLD-resistant fragment of Montastraea cavernosa , as a potential probiotic treatment for SCTLD-infected M. cavernosa colonies in the wild. We developed and tested two probiotic deployment methods: (1) the injection of a probiotic in seawater suspension into a weighted bag placed over the coral to treat the whole colony; and (2) a sodium alginate-based paste that was applied directly to each disease lesion. After treatment, the disease progression of each colony was routinely monitored using three-dimensional photogrammetry for 2.5 years. Slurries of tissue and mucus samples were taken from healthy and diseased colonies before treatment, two weeks after treatment, and three months after treatment to identify possible shifts in bacterial and archaeal communities. McH1–7 successfully slowed SCTLD lesion progression for 2.5 years following treatments when delivered using the whole-colony treatment technique. Our assessment of the microbiome following treatment showed that McH1–7 was effective without dominating bacterial communities among infected corals. In contrast, corals treated with the probiotic paste lost more tissue than corals treated with the control paste, indicating that the lesion-specific probiotic paste is not effective at stopping SCTLD. Probiotic inoculations via a whole-colony treatment technique may provide a path toward slowing the loss of reef-building corals due to SCTLD.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Endothelial IGF- 1R deficiency disrupts microvascular homeostasis, impairing skeletal muscle perfusion and endurance: implications for age-related sarcopenia - Adam Nyul-Toth; Santny Shanmugarama; Roland Patai; Rafal Gulej; Janet Faakye; Dorina Nagy; Mark Nagykaldi; Tamas Kiss; Tamas Csipo; Madison Milan; Shoba Ekambaram; Sharon Negri; et al. (GeroScience, 2025)
Aging is associated with a progressive decline in circulating insulin-like growth factor- 1 (IGF- 1) levels in humans, which has been implicated in the pathogenesis of sarcopenia. IGF- 1 is an anabolic hormone that plays a dual role in maintaining skeletal muscle health, acting both directly on muscle fibers to promote growth and indirectly by supporting the vascular network that sustains muscle perfusion. However, the microvascular consequences of IGF- 1 deficiency in aging muscle remain poorly understood. To elucidate how impaired IGF- 1 input affects skeletal muscle vasculature, we examined the effects of endothelial-specific IGF- 1 receptor (IGF- 1R) deficiency using a mouse model of endothelial IGF- 1R knockdown (VE-Cadherin-CreER T2 /Igf1r f/f mice). These mice exhibited significantly reduced skeletal muscle endurance and attenuated hyperemic response to acetylcholine, an endothelium-dependent vasodilator. Additionally, they displayed microvascular rarefaction and impaired nitric oxide-dependent vasorelaxation, indicating a significant decline in microvascular health in skeletal muscle. These findings suggest that endothelial IGF- 1R signaling is critical for maintaining microvascular integrity, muscle perfusion, and function. Impaired IGF- 1 input to the microvascular endothelium may contribute to reduced muscle blood flow and exacerbate age-related sarcopenia. Enhancing vascular health by modulating IGF- 1 signaling could represent a potential therapeutic strategy to counteract age-related muscle decline.

Net ecosystem carbon budget and net greenhouse gas emissions under diverse crop rotation using cover crops compared to a conventional crop rotation - Keerthika N. Ranathunga; Jacob Evans; Nikolett Toth; Shannon Brown; Laura L. Van Eerd; Claudia Wagner-Riddle (Agriculture, Ecosystems & Environment, 2025)

Insecticide application prevents honey bees from realizing benefits of native forage in an agricultural landscape - Ashley L. St. Clair; Adam G. Dolezal; Randall P. Cass; Harmen P. Hendriksma; David S. Stein; Kate E. Borchardt; Erin W. Hodgson; Matthew E. O'Neal; Amy L. Toth (Science of The Total Environment, 2025)

Too hot to handle? The impact of the 2023 marine heatwave on Florida Keys coral - Karen L. Neely; Robert J. Nowicki; Michelle A. Dobler; Arelys A. Chaparro; Samantha M. Miller; Kathryn A. Toth (Frontiers in Marine Science, 2024)
The summer 2023 marine heatwave was the most severe on record for Florida’s Coral Reef, with unprecedented water temperatures and cumulative heat stress leading to 100% coral bleaching. An existing fate-tracking program of over 4200 brain and boulder coral colonies across five offshore and four inshore reefs allowed for analyses of bleaching-related mortality and diseases through the event. Across the vast majority of assessed corals, there was no partial or full mortality as a result of the 2023 bleaching event. At seven of the nine sites, only 0 – 2% of fate-tracked colonies experienced any mortality. The other two sites, both inshore, had the highest cumulative heat stress and did experience substantial bleaching-related mortality. However, acute mortality at one of them began at relatively low cumulative heat stress, suggesting death was the result of exceeding thermal maxima rather than bleaching-related resource depletion. At the two most impacted sites, 43% and 30% of all monitored corals died, but mortality varied among species: brain corals fared worse than boulder corals. The health status of corals before the bleaching event had little impact on whether they exhibited mortality during the event. At three sites, we observed unusual lesions on Orbicella faveolata colonies shortly after color returned to the corals; these were only present for a few months, but on some colonies led to substantial tissue loss. Though not part of the monitoring program, we also observed local extinctions of Acroporid corals at most sites, as well as local extinctions of octocorals at three inshore reefs. Though most reef-building corals survived the 2023 marine heatwave in the Florida Keys, continually rising temperatures are likely to make these temperature regimes more common. We encourage future research on why the brain and boulder corals fared differently at highly-impacted sites, and on what the unusual O. faveolata lesions are. Our results also provide perspective on how restoration strategies, particularly those focused on species likely to die under current and future climate regimes, might prioritize species likely to survive. Finally, these results highlight the importance of fate-tracking individuals of different species and in different geographies and habitat types through disturbance events.

Is the genetic architecture of behavior exceptionally complex? - Cameron R Fay; Amy L Toth (Current Opinion in Insect Science, 2024)

Vascular smooth muscle cell-specific Igf1r deficiency exacerbates the development of hypertension-induced cerebral microhemorrhages and gait defects - Lauren R. Miller; Marisa A. Bickel; Michaela L. Vance; Hannah Vaden; Domonkos Nagykaldi; Adam Nyul-Toth; Elizabeth C. Bullen; Tripti Gautam; Stefano Tarantini; Andriy Yabluchanskiy; Tamas Kiss; Zoltan Ungvari; et al. (GeroScience, 2024)

Broadscale coral disease interventions elicit efficiencies in endemic disease response - Kathryn A. Toth; Samantha F. Buckley; Hunter Noren; Karen L. Neely; Brian K. Walker (Frontiers in Marine Science, 2024)
The presence and abundance of reef-building corals are crucial to the long-term existence of Caribbean coral reef ecosystems, providing both direct and indirect, local and global, ecological, economic, and social benefits. In 2014, stony coral tissue loss disease (SCTLD) was first identified in southeast Florida and remains endemic to the region, while continuing to spread throughout the Caribbean. Effective in situ intervention treatments using antibiotic paste can halt lesion progression on Montastraea cavernosa up to 90% of the time. This study investigated intervention activities over a three-year period to identify efficiencies in disease response. Since May 2019, 1,037 corals, >85% of which were M. cavernosa , were treated during disease intervention dives in southeast Florida. Treated coral density, the number of treated corals per meter along a dive track, was significantly higher in the first year compared to subsequent years and displayed annual peaks in late summer each year. Season significantly influenced treatment density, leading to higher values in the wet season across all years, 2019 to 2022. Areas of highest treatment density were identified between Haulover Inlet and Government Cut near Miami and Hillsboro Inlet in northern Broward County. Areas with the highest treatment density were only identified in the first year, suggesting that broadscale interventions may have decreased disease prevalence in subsequent years. Results indicate that in endemic areas with sporadic and dynamic disease prevalence, intervention efforts should be weighted proportionally across space and time to maximize intervention efficiency. This study provides optimistic results for the potential of interventions reducing disease prevalence and supports that disease interventions are an effective coral restoration tool that can decrease the increasing burden on post hoc coral restoration.

An ecological networks approach reveals restored native vegetation benefits wild bees in agroecosystems - Kate E. Borchardt; Claus Kadelka; Lisa A. Schulte; Amy L. Toth (Biological Conservation, 2023)

Nutritional inequalities structure worker division of labor in social insects - Alexander Walton; Amy L Toth (Current Opinion in Insect Science, 2023)

A practical approach to RNA interference for studying gene function in a refractory social insect (on a limited budget) - A. Walton; E. Flores; A. Guinness; R. Fortune; M. J. Sheehan; A. L. Toth (Insectes Sociaux, 2023)

Correction to: Genetic structure and diversity of the mustard hill coral Porites astreoides along the Florida Keys reef tract - Dominique N. Gallery; Michelle L. Green; Ilsa B. Kuffner; Elizabeth A. Lenz; Lauren T. Toth (Marine Biodiversity, 2021)

Genetic structure and diversity of the mustard hill coral Porites astreoides along the Florida Keys reef tract - Dominique N. Gallery; Michelle L. Green; Ilsa B. Kuffner; Elizabeth A. Lenz; Lauren T. Toth (Marine Biodiversity, 2021)
Increases in local and global stressors have led to major declines in coral populations throughout the western Atlantic. While abundances of other species have declined, however, the relative abundance of the mustard hill coral, Porites astreoides , has increased. Porites astreoides is relatively resilient to some stressors, and because of its mixed reproductive strategies, its populations often recover quickly following disturbances. The ability for P. astreoides to continue as a potential “winner” in western Atlantic reefs relies on maintaining sufficient genetic variation within populations to support acclimatization and adaptation to current and future environmental change. Without high genetic diversity and gene flow within the population, it would have limited capacity for adaptation and the species’ competitive advantages could be short-lived. In this study, we determined the genetic relatedness of 37 P. astreoides colonies at four shallow reefs along the offshore Florida Keys Reef Tract (FKRT), a region particularly hard-hit by recent disturbances. Using previously designed microsatellite markers, we determined the genetic diversity and connectivity of individuals among and between sites. Our results suggest that the FKRT likely contains a single, well-mixed genetic population of P. astreoides , with high levels of gene flow and evidence for larval migration throughout the region. This suggests that regional populations of P. astreoides likely have a higher chance of maintaining resilience than many other western Atlantic species as they face current and future disturbances.

Diagnostic muscle biopsies in the era of genetics: the added value of myopathology in a selection of limb-girdle muscular dystrophy patients - Boel De Paepe; Elise Velghe; Linnea Salminen; Balint Toth; Pieter Olivier; Jan L. De Bleecker (Acta Neurologica Belgica, 2021)

How much leaf area do insects eat? A data set of insect herbivory sampled globally with a standardized protocol - Gisele M. Mendes; Fernando A. O. Silveira; Carolina Oliveira; Wesley Dáttilo; Roger Guevara; Betsabé Ruiz‐Guerra; Maria Gabriela Boaventura; Sershen; Syd Ramdhani; Shyam S. Phartyal; Sérvio P. Ribeiro; Victor Diniz Pinto; et al. (Ecology, 2021)
Herbivory is ubiquitous. Despite being a potential driver of plant distribution and performance, herbivory remains largely undocumented. Some early attempts have been made to review, globally, how much leaf area is removed through insect feeding. Kozlov et al., in one of the most comprehensive reviews regarding global patterns of herbivory, have compiled published studies regarding foliar removal and sampled data on global herbivory levels using a standardized protocol. However, in the review by Kozlov et al., only 15 sampling sites, comprising 33 plant species, were evaluated in tropical areas around the globe. In Brazil, which ranks first in terms of plant biodiversity, with a total of 46,097 species, almost half (43%) being endemic, a single data point was sampled, covering only two plant species. In an attempt to increase knowledge regarding herbivory in tropical plant species and to provide the raw data needed to test general hypotheses related to plant–herbivore interactions across large spatial scales, we proposed a joint, collaborative network to evaluate tropical herbivory. This network allowed us to update and expand the data on insect herbivory in tropical and temperate plant species. Our data set, collected with a standardized protocol, covers 45 sampling sites from nine countries and includes leaf herbivory measurements of 57,239 leaves from 209 species of vascular plants belonging to 65 families from tropical and temperate regions. They expand previous data sets by including a total of 32 sampling sites from tropical areas around the globe, comprising 152 species, 146 of them being sampled in Brazil. For temperate areas, it includes 13 sampling sites, comprising 59 species. Thus, when compared to the most recent comprehensive review of insect herbivory (Kozlov et al.), our data set has increased the base of available data for the tropical plants more than 460% (from 33 to 152 species) and the Brazilian sampling was increased 7,300% (from 2 to 146 species). Data on precise levels of herbivory are presented for more than 57,000 leaves worldwide. There are no copyright restrictions. Please cite this paper when using the current data in publications; the authors request to be informed how the data is used in the publications.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

10th Anniversary of the European Association for Predictive, Preventive and Personalised (3P) Medicine - EPMA World Congress Supplement 2020 - Olga Golubnitschaja; Ondrej Topolcan; Radek Kucera; Vincenzo Costigliola; M. Akopyan; S. N. Akulov; O Alexandrova; Angel Alonso; Russell J. Andrews; A Assuane Duarte; O. Azarova; Maximilian Babel; et al. (EPMA Journal, 2020)
In 2019, the EPMA celebrated its 10th anniversary at the 5th World Congress in Pilsen, Czech Republic. The history of the International Professional Network dedicated to Predictive, Preventive and Personalised Medicine (PPPM / 3PM) is rich in achievements. Facing the coronavirus COVID-19 pandemic it is getting evident globally that the predictive approach, targeted prevention and personalisation of medical services is the optimal paradigm in healthcare demonstrating the high potential to save lives and to benefit the society as a whole. The EPMA World Congress Supplement 2020 highlights advances in 3P medicine.

7700-year persistence of an isolated, free-living coral assemblage in the Galápagos Islands: a model for coral refugia? - J. S. Feingold; B. Riegl; K. Hendrickson; L. T. Toth; H. Cheng; R. L. Edwards; R. B. Aronson (Coral Reefs, 2020)

Pharmacological or genetic depletion of senescent astrocytes prevents whole brain irradiation–induced impairment of neurovascular coupling responses protecting cognitive function in mice - Andriy Yabluchanskiy; Stefano Tarantini; Priya Balasubramanian; Tamas Kiss; Tamas Csipo; Gábor A. Fülöp; Agnes Lipecz; Chetan Ahire; Jordan DelFavero; Adam Nyul-Toth; William E. Sonntag; Michal L. Schwartzman; et al. (GeroScience, 2020)

Upwelling buffers climate change impacts on coral reefs of the eastern tropical Pacific - Carly J. Randall; Lauren T. Toth; James J. Leichter; Juan L. Maté; Richard B. Aronson (Ecology, 2020)
Corals of the eastern tropical Pacific live in a marginal and oceanographically dynamic environment. Along the Pacific coast of Panamá, stronger seasonal upwelling in the Gulf of Panamá in the east transitions to weaker upwelling in the Gulf of Chiriquí in the west, resulting in complex regional oceanographic conditions that drive differential coral‐reef growth. Over millennial timescales, reefs in the Gulf of Chiriquí recovered more quickly from climatic disturbances compared with reefs in the Gulf of Panamá. In recent decades, corals in the Gulf of Chiriquí have also had higher growth rates than in the Gulf of Panamá. As the ocean continues to warm, however, conditions could shift to favor the growth of corals in the Gulf of Panamá, where upwelling may confer protection from high‐temperature anomalies. Here we describe the recent spatial and temporal variability in surface oceanography of nearshore environments in Pacific Panamá and compare those conditions with the dynamics of contemporary coral‐reef communities during and after the 2016 coral‐bleaching event. Although both gulfs have warmed significantly over the last 150 yr, the annual thermal maximum in the Gulf of Chiriquí is increasing faster, and ocean temperatures there are becoming more variable than in the recent past. In contrast to historical trends, we found that coral cover, coral survival, and coral growth rates were all significantly higher in the Gulf of Panamá. Corals bleached extensively in the Gulf of Chiriquí following the 2015–2016 El Niño event, whereas upwelling in the Gulf of Panamá moderated the high temperatures caused by El Niño, allowing the corals largely to escape thermal stress. As the climate continues to warm, upwelling zones may offer a temporary and localized refuge from the thermal impacts of climate change, while reef growth in the rest of the eastern tropical Pacific continues to decline.

Influence of Perinatal Polychlorinated Biphenyl or Thiouracil on Dopamine Function - Cynthia L. Toth; David E. Mankin; Katie A. Hiler; Nicholas A.F. Baldwin; Lee A. Meserve; Howard C. Cromwell (Toxicology and Environmental Health Sciences, 2019)

The unprecedented loss of Florida's reef‐building corals and the emergence of a novel coral‐reef assemblage - L. T. Toth; A. Stathakopoulos; I. B. Kuffner; R. R. Ruzicka; M. A. Colella; E. A. Shinn (Ecology, 2019)
Over the last half century, climate change, coral disease, and other anthropogenic disturbances have restructured coral‐reef ecosystems on a global scale. The disproportionate loss of once‐dominant, reef‐building taxa has facilitated relative increases in the abundance of “weedy” or stress‐tolerant coral species. Although the recent transformation of coral‐reef assemblages is unprecedented on ecological timescales, determining whether modern coral reefs have truly reached a novel ecosystem state requires evaluating the dynamics of reef composition over much longer periods of time. Here, we provide a geologic perspective on the shifting composition of Florida's reefs by reconstructing the millennial‐scale spatial and temporal variability in reef assemblages using 59 Holocene reef cores collected throughout the Florida Keys Reef Tract ( FKRT ). We then compare the relative abundances of reef‐building species in the Holocene reef framework to data from contemporary reef surveys to determine how much Florida's modern reef assemblages have diverged from long‐term baselines. We show that the composition of Florida's reefs was, until recently, remarkably stable over the last 8000 yr. The same corals that have dominated shallow‐water reefs throughout the western Atlantic for hundreds of thousands of years, Acropora palmata , Orbicella spp., and other massive coral taxa, accounted for nearly 90% of Florida's Holocene reef framework. In contrast, the species that now have the highest relative abundances on the FKRT , primarily Porites astreoides and Siderastrea siderea , were rare in the reef framework, suggesting that recent shifts in species assemblages are unprecedented over millennial timescales. Although it may not be possible to return coral reefs to pre‐Anthropocene states, our results suggest that coral‐reef management focused on the conservation and restoration of the reef‐building species of the past, will optimize efforts to preserve coral reefs, and the valuable ecosystem services they provide into the future.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Candidate genes for cooperation and aggression in the social wasp Polistes dominula - Fabio Manfredini; Mark J. F. Brown; Amy L. Toth (Journal of Comparative Physiology A, 2018)

To reproduce or work? Insect castes emerge from socially induced changes in nutrition‐related genes - Amy L. Toth (Molecular Ecology, 2017)
In social species, there is a fundamental trade‐off between ‘me’ and ‘we’; that is, should I reproduce, or should I work to help others to reproduce? In this issue of Molecular Ecology , Okada et al . ( ) delve into the evolution and genetic mechanisms of this core question, focusing on social caste formation in insects. The authors take advantage of a unique ant in the genus Diacamma , which has secondarily lost the classic, highly different queens and workers found in many other ants, bees and wasps. Instead, Diacamma ant castes are decided via aggressive dominance interactions among adult females, similar to dominance hierarchies seen in primitively social insects and many social vertebrates. But how does being dominated translate into reproductive shutdown and thus, the creation of a worker caste? The authors use transcriptomics to address this question, and discover that the key may lie in very rapid (within one day) changes in the regulation of nutrient signalling genes, and other genes related to nutrient storage and reproduction. In other words, being aggressed turns on or off genes that tell the ant's brain and physiology to go into ‘sterile mode’, whereas winning a fight stimulates other genes that ramp up reproductive traits. These results add weight to the idea that caste differences rely on a ‘toolkit’ of deeply conserved genes involved in core nutritional, reproductive and metabolic functions. In addition, these results emphasize the exquisite and rapid social environmental sensitivity of core toolkit genes during the production of distinct phenotypes.

Variation in individual worker honey bee behavior shows hallmarks of personality - Alexander Walton; Amy L. Toth (Behavioral Ecology and Sociobiology, 2016)

Genome, transcriptome and methylome sequencing of a primitively eusocial wasp reveal a greatly reduced DNA methylation system in a social insect - Daniel S. Standage; Ali J. Berens; Karl M. Glastad; Andrew J. Severin; Volker P. Brendel; Amy L. Toth (Molecular Ecology, 2016)
Comparative genomics of social insects has been intensely pursued in recent years with the goal of providing insights into the evolution of social behaviour and its underlying genomic and epigenomic basis. However, the comparative approach has been hampered by a paucity of data on some of the most informative social forms (e.g. incipiently and primitively social) and taxa (especially members of the wasp family Vespidae) for studying social evolution. Here, we provide a draft genome of the primitively eusocial model insect Polistes dominula , accompanied by analysis of caste‐related transcriptome and methylome sequence data for adult queens and workers. Polistes dominula possesses a fairly typical hymenopteran genome, but shows very low genomewide GC content and some evidence of reduced genome size. We found numerous caste‐related differences in gene expression, with evidence that both conserved and novel genes are related to caste differences. Most strikingly, these –omics data reveal a major reduction in one of the major epigenetic mechanisms that has been previously suggested to be important for caste differences in social insects: DNA methylation. Along with a conspicuous loss of a key gene associated with environmentally responsive DNA methylation (the de novo DNA methyltransferase Dnmt3 ), these wasps have greatly reduced genomewide methylation to almost zero. In addition to providing a valuable resource for comparative analysis of social insect evolution, our integrative –omics data for this important behavioural and evolutionary model system call into question the general importance of DNA methylation in caste differences and evolution in social insects.

Candidate genes for individual recognition in Polistes fuscatus paper wasps - A. J. Berens; E. A. Tibbetts; A. L. Toth (Journal of Comparative Physiology A, 2016)

Different axes of environmental variation explain the presence vs. extent of cooperative nest founding associations in Polistes paper wasps - Michael J Sheehan; Carlos A Botero; Tory A Hendry; Brian E Sedio; Jennifer M Jandt; Susan Weiner; Amy L Toth; Elizabeth A Tibbetts (Ecology Letters, 2015)
Ecological constraints on independent breeding are recognised as major drivers of cooperative breeding across diverse lineages. How the prevalence and degree of cooperative breeding relates to ecological variation remains unresolved. Using a large data set of cooperative nesting in Polistes wasps we demonstrate that different aspects of cooperative breeding are likely to be driven by different aspects of climate. Whether or not a species forms cooperative groups is associated with greater short‐term temperature fluctuations. In contrast, the number of cooperative foundresses increases in more benign environments with warmer, wetter conditions. The same data set reveals that intraspecific responses to climate variation do not mirror genus‐wide trends and instead are highly heterogeneous among species. Collectively these data suggest that the ecological drivers that lead to the origin or loss of cooperation are different from those that influence the extent of its expression within populations.

Enhanced Transdermal Peptide Delivery and Stability by Lipid Conjugation: Epidermal Permeation, Stereoselectivity and Mechanistic Insights - Sarika Namjoshi; Istvan Toth; Joanne T. Blanchfield; Nicholas Trotter; Ricardo L. Mancera; Heather A. E. Benson (Pharmaceutical Research, 2014)

Investigation of the Possible Functions of PACAP in Human Trophoblast Cells - G. Horvath; D. Reglodi; R. Brubel; M. Halasz; A. Barakonyi; A. Tamas; E. Fabian; B. Opper; G. Toth; M. Cohen; L. Szereday (Journal of Molecular Neuroscience, 2014)

Do no-take reserves benefit Florida’s corals? 14 years of change and stasis in the Florida Keys National Marine Sanctuary - L. T. Toth; R. van Woesik; T. J. T. Murdoch; S. R. Smith; J. C. Ogden; W. F. Precht; R. B. Aronson (Coral Reefs, 2014)

Flagella interact with ionic plant lipids to mediate adherence of pathogenic Escherichia coli to fresh produce plants - Yannick Rossez; Ashleigh Holmes; Eliza B. Wolfson; David L. Gally; Arvind Mahajan; Henriette L. Pedersen; William G.T. Willats; Ian K. Toth; Nicola J. Holden (Environmental Microbiology, 2014)
Summary Bacterial attachment to plant and animal surfaces is generally thought to constitute the initial step in colonization, requiring adherence factors such as flagella and fimbriae. We describe the molecular mechanism underpinning flagella‐mediated adherence to plant tissue for the foodborne pathogen, enterohaemorrhagic E scherichia coli . E scherichia coli H 7 flagella interacted with a sulphated carbohydrate (carrageenan) on a glycan array, which occurred in a dose‐dependent manner. Adherence of E . coli O 157 : H ‐expressing flagella of serotype H 7, H 6 or H 48 to plants associated with outbreaks from fresh produce and to A rabidopsis thaliana , was dependent on flagella interactions with phospholipids and sulpholipids in plasma membranes. Adherence of purified H 7 and H 48 flagella to carrageenan was reduced at higher concentrations of KH 2 PO 4 or KCl , showing an ionic basis to the interactions. Purified H 7 flagella were observed to physically interact with plasma membranes in spinach plants and in A . thaliana . The results show a specific interaction between E . coli H 7, H 6 and H 48 flagella and ionic lipids in plant plasma membranes. The work extends our understanding of the molecular mechanisms underpinning E . coli flagella targeting of plant hosts and suggests a generic mechanism of recognition common in eukaryotic hosts belonging to different biological kingdoms.

A depth refugium from catastrophic coral bleaching prevents regional extinction - Tyler B. Smith; Peter W. Glynn; Juan L. Maté; Lauren T. Toth; Joanna Gyory (Ecology, 2014)
Species intolerant of changing climate might avoid extinction within refugia buffered from extreme conditions. Refugia have been observed in the fossil record but are not well documented or understood on ecological time scales. Using a 37‐year record from the eastern Pacific across the two most severe El Niño events on record (1982–1983 and 1997–1998) we show how an exceptionally thermally sensitive reef‐building hydrocoral, Millepora intricata , twice survived catastrophic bleaching in a deeper‐water refuge (>11 m depth). During both events, M. intricata was extirpated across its range in shallow water, but showed recovery within several years, while two other hydrocorals without deep‐water populations were driven to regional extinction. Evidence from the subfossil record in the same area showed shallow‐water persistence of abundant M. intricata populations from 5000 years ago, through severe El Niño–Southern Oscillation cycles, suggesting a potential depth refugium on a millennial timescale. Our data confirm the deep refuge hypothesis for corals under thermal stress.

Polistes paper wasps: a model genus for the study of social dominance hierarchies - J. M. Jandt; E. A. Tibbetts; A. L. Toth (Insectes Sociaux, 2014)

The role of PKC signaling in CRF-induced modulation of startle - M. Toth; J. E. Gresack; R. L. Hauger; A. L. Halberstadt; V. B. Risbrough (Psychopharmacology, 2013)

Cardiac glutaminolysis: a maladaptive cancer metabolism pathway in the right ventricle in pulmonary hypertension - Lin Piao; Yong-Hu Fang; Kishan Parikh; John J. Ryan; Peter T. Toth; Stephen L. Archer (Journal of Molecular Medicine, 2013)

A survey of DNA methylation across social insect species, life stages, and castes reveals abundant and caste-associated methylation in a primitively social wasp - Susan A. Weiner; David A. Galbraith; Dean C. Adams; Nicole Valenzuela; Fernando B. Noll; Christina M. Grozinger; Amy L. Toth (The Science of Nature, 2013)

FOXO1-mediated upregulation of pyruvate dehydrogenase kinase-4 (PDK4) decreases glucose oxidation and impairs right ventricular function in pulmonary hypertension: therapeutic benefits of dichloroacetate - Lin Piao; Vaninder K. Sidhu; Yong-Hu Fang; John J. Ryan; Kishan S. Parikh; Zhigang Hong; Peter T. Toth; Erik Morrow; Shelby Kutty; Gary D. Lopaschuk; Stephen L. Archer (Journal of Molecular Medicine, 2013)

Effects of PACAP on Intracellular Signaling Pathways in Human Retinal Pigment Epithelial Cells Exposed to Oxidative Stress - E. Fabian; D. Reglodi; L. Mester; A. Szabo; K. Szabadfi; A. Tamas; G. Toth; K. Kovacs (Journal of Molecular Neuroscience, 2012)

Effects of Pituitary Adenylate Cyclase Activating Polypeptide on Human Sperm Motility - R. Brubel; P. Kiss; A. Vincze; A. Varga; A. Varnagy; J. Bodis; L. Mark; E. Jambor; G. Maasz; H. Hashimoto; Zs. Helyes; G. Toth; et al. (Journal of Molecular Neuroscience, 2012)

Defining bottlenose dolphin ( Tursiops truncatus ) stocks based on environmental, physical, and behavioral characteristics - Jacalyn L. Toth; Aleta A. Hohn; Kenneth W. Able; Antoinette M. Gorgone (Marine Mammal Science, 2012)
The population structure of bottlenose dolphins, Tursiops truncatus , along the U.S. Atlantic coast has recently been redefined from one homogenous population into five coastal stocks. Local studies indicate even finer structure, primarily based on isolation of dolphins inhabiting estuaries. We identified population structuring of non‐estuarine coastal bottlenose dolphins during a study in New Jersey, the northern range along the Atlantic Coast. Using photo‐identification and distribution survey results, an analysis identified two major clusters of individuals significantly separated by five variables (distance from shoreline, group size, occurrence of the barnacle Xenobalanus globicipitis , avoidance behavior, and individual coloration). Sightings assigned to cluster 1 occurred in nearshore shallow waters (0–1.9 km, x̄ = 3.5 m), and those assigned to cluster 2 occurred further offshore in deeper waters (1.9–6 km, x̄ = 9.5 m). Only eight of 194 individuals (4%) were identified in both regions. Collectively, this suggests an occurrence of two stocks that are spatially, physically, and behaviorally distinguishable over a small distance. These results indicate that complexity in Tursiops population structure is not limited to latitudinal gradients or barriers created by estuarine habitats, but also by partitioning of habitat as a function of distance from shore and depth over small distances.

Therapeutic inhibition of fatty acid oxidation in right ventricular hypertrophy: exploiting Randle’s cycle - Yong-Hu Fang; Lin Piao; Zhigang Hong; Peter T. Toth; Glenn Marsboom; Peter Bache-Wiig; Jalees Rehman; Stephen L. Archer (Journal of Molecular Medicine, 2012)

Nutrition and division of labor: Effects on foraging and brain gene expression in the paper wasp Polistes metricus - T. H. F. DAUGHERTY; A. L. TOTH; G. E. ROBINSON (Molecular Ecology, 2011)
Deeply conserved molecular mechanisms regulate food‐searching behaviour in response to nutritional cues in a wide variety of vertebrates and invertebrates. Studies of the highly eusocial honey bee have shown that nutritional physiology and some conserved nutrient signalling pathways, especially the insulin pathway, also regulate the division of labour between foraging and non‐foraging individuals. Typically, lean workers leave the nest to forage for food, and well‐nourished workers perform tasks inside the nest. Here we provide the first direct test of whether similar mechanisms operate in a primitively eusocial insect in an independently evolved social lineage, the paper wasp Polistes metricus . We found that food deprivation caused reduced lipid stores and higher levels of colony and individual foraging. Individuals with greatly reduced lipid stores foraged at extremely elevated levels. In addition, brain expression of several foraging‐related genes was influenced by food deprivation, including insulin‐like peptide 2 ( ilp2 ). Together with previous findings, our results demonstrate that nutrition regulates foraging division of labour in two independently evolved social insect lineages (bees and wasps), despite large differences in social organization. Our results also provide additional support for the idea that nutritional asymmetries among individuals, based on differences in nutritional physiology and expression of conserved nutrient signalling genes in the brain, are important in the division of labour in eusocial societies.

Development of new microsatellite loci for the genus Polistes from publicly available expressed sequence tag sequences - M. T. Henshaw; A. L. Toth; T. J. Young (Insectes Sociaux, 2011)

Patterns of seasonal occurrence, distribution, and site fidelity of coastal bottlenose dolphins ( Tursiops truncatus ) in southern New Jersey, U.S.A. - Jacalyn L. Toth; Aleta A. Hohn; Kenneth W. Able; Antoinette M. Gorgone (Marine Mammal Science, 2011)
Coastal bottlenose dolphins ( Tursiops truncatus ) form a mosaic of resident and seasonal migratory populations along the United States Atlantic seaboard. Seasonal, poorly known migrants (identified as a separate stock) move as far north as New Jersey. During 2003–2005, 73 boat‐based photo‐identification surveys were conducted in southern New Jersey to discern seasonal occurrence, distribution, and patterns of movement and site fidelity. Neonates, young‐of‐year, and adults occurred in the study area from late May through late September, corresponding to water temperatures of 14.0–16.3°C. Of 205 individuals identified, 44% ( n = 90) were sighted multiple times within or among years, including 10% ( n = 20) of individuals identified in all 3 yr. Almost half (47%) of the multiple sightings were observed along a core area encompassed by the southern part of the Jacques Cousteau National Estuarine Research Reserve. In contrast to stocks studied in southern coastal areas of the U.S. Atlantic and Gulf of Mexico, estuaries were used significantly less than open‐beach habitat, which is consistent with the relative prey abundance in these habitats. Research at additional sites will help confirm whether bottlenose dolphins at the northern end of their migratory range exhibit local site fidelity and habitat preferences similar to those found in this study.

Changes in the Expression of Pituitary Adenylate Cyclase-Activating Polypeptide in the Human Placenta during Pregnancy and Its Effects on the Survival of JAR Choriocarcinoma Cells - R. Brubel; A. Boronkai; D. Reglodi; B. Racz; J. Nemeth; P. Kiss; A. Lubics; G. Toth; G. Horvath; T. Varga; D. Szogyi; E. Fonagy; et al. (Journal of Molecular Neuroscience, 2010)

The inhibition of pyruvate dehydrogenase kinase improves impaired cardiac function and electrical remodeling in two models of right ventricular hypertrophy: resuscitating the hibernating right ventricle - Lin Piao; Yong-Hu Fang; Virgilio J. J. Cadete; Christian Wietholt; Dalia Urboniene; Peter T. Toth; Glenn Marsboom; Hannah J. Zhang; Idith Haber; Jalees Rehman; Gary D. Lopaschuk; Stephen L. Archer (Journal of Molecular Medicine, 2010)

Lipid stores, ovary development, and brain gene expression in Polistes metricus females - A. L. Toth; K. B. J. Bilof; M. T. Henshaw; J. H. Hunt; G. E. Robinson (Insectes Sociaux, 2009)

Abrupt climate change near the poles - Klaus Keller; Richard S. J. Tol; Ferenc L. Toth; Gary W. Yohe (Climatic Change, 2008)

Managing the inconceivable: participatory assessments of impacts and responses to extreme climate change - Ferenc L. Toth; Eva Hizsnyik (Climatic Change, 2008)

Ecological threshold responses in European lakes and their applicability for the Water Framework Directive (WFD) implementation: synthesis of lakes results from the REBECCA project - Anne Lyche Solheim; Seppo Rekolainen; S. Jannicke Moe; Laurence Carvalho; Geoff Phillips; Robert Ptacnik; W. Ellis Penning; Laszlo G. Toth; Constance O’Toole; Ann-Kristin L. Schartau; Trygve Hesthagen (Aquatic Ecology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

In vivo actions of aripiprazole on serotonergic and dopaminergic systems in rodent brain - A. Bortolozzi; L. Díaz-Mataix; M. Toth; P. Celada; F. Artigas (Psychopharmacology, 2007)

Climate Change, Flow Regulation and Land-Use Effects on the Hydrology of the Peace-Athabasca-Slave System; Findings from the Northern Rivers Ecosystem Initiative - T. D. Prowse; S. Beltaos; J. T. Gardner; J. J. Gibson; R. J. Granger; R. Leconte; D. L. Peters; A. Pietroniro; L. A. Romolo; B. Toth (Environmental Monitoring and Assessment, 2006)

The highly efficacious actions of N-desmethylclozapine at muscarinic receptors are unique and not a common property of either typical or atypical antipsychotic drugs: is M1 agonism a pre-requisite for mimicking clozapine?s actions? - Marilyn A. Davies; Beth Ann Compton-Toth; Sandra J. Hufeisen; Herbert Y. Meltzer; Bryan L. Roth (Psychopharmacology, 2005)

The Path from Molecular Indicators of Exposure to Describing Dynamic Biological Systems in an Aquatic Organism: Microarrays and the Fathead Minnow - Ann L. Miracle; Gregory P. Toth; David L. Lattier (Ecotoxicology, 2003)

Economic Development and Emission Control over the Long Term: The ICLIPS Aggregated Economic Model - Marian Leimbach; Ferenc L. Toth (Climatic Change, 2003)

Methodological Aspects of the Tolerable Windows Approach - Thomas Bruckner; Gerhard Petschel-Held; Marian Leimbach; Ferenc L. Toth (Climatic Change, 2003)

Integrated Assessment of Long-term Climate Policies: Part 2 – Model Results and Uncertainty Analysis - Ferenc L. Toth; Thomas Bruckner; Hans-Martin Füssel; Marian Leimbach; Gerhard Petschel-Held (Climatic Change, 2003)

Climate Policy in Light of Climate Science: The ICLIPS Project - Ferenc L. Toth (Climatic Change, 2003)

Climate Impact Response Functions as Impact Tools in the Tolerable Windows Approach - H.-M. Füssel; F. L. Toth; J. G. van Minnen; F. Kaspar (Climatic Change, 2003)

Integrated Assessment of Long-term Climate Policies: Part 1 – Model Presentation - Ferenc L. Toth; Thomas Bruckner; Hans-Martin Füssel; Marian Leimbach; Gerhard Petschel-Held (Climatic Change, 2003)

Integrated Assessment of Climate Protection Strategies - Ferenc L. Toth (Climatic Change, 2003)

Modified crystal violet pectate medium (CVP) based on a new polypectate source (Slendid) for the detection and isolation of soft rot erwinias - L. J. Hyman; L. Sullivan; I. K. Toth; M. C. M. Perombelon (Potato Research, 2001)

Climate Impact Response Functions: An Introduction - Ferenc L. Toth; Wolfgang Cramer; Eva Hizsnyik (Climatic Change, 2000)

Adaptation and the Guardrail Approach to Tolerable Climate Change - Gary Yohe; Ferenc L. Toth (Climatic Change, 2000)

Regulation of the apolipoprotein B in heterozygous hypobeta-lipoproteinemic knock-out mice expressing truncated apoB, B81. Low production and enhanced clearance of apoB cause low levels of apoB - Rai Ajit K. Srivastava; L. Toth; Neelam Srivastava; Myron E. Hinsdale; Nobuyo Maeda; A.B. Cefalu´; Maurizio Averna; Gustav Schonfeld (Molecular and Cellular Biochemistry, 1999)

Integrated environmental assessment methods: Evolution and applications - Ferenc L. Toth; Eva Hizsnyik (Environmental Modeling & Assessment, 1998)

Preliminary Studies on the Population Genetics of the Central Stoneroller (Campostoma anomalum) from the Great Miami River Basin, Ohio - R. N. Silbiger; S. A. Christ; A. C. Leonard; M. Garg; D. L. Lattier; S. Dawes; P. Dimsoski; F. McCormick; T. Wessendarp; D. A. Gordon; A.C. Roth; M. K. Smith; et al. (Environmental Monitoring and Assessment, 1998)

The sterilizing effect of ethylene oxide vapor on different micro-organisms - L. Z. J. Toth (Archives of Microbiology, 1959)